Synthesis and biological evaluation of novel selective androgen receptor modulators (SARMs) Part III: Discovery of 4-(5-oxopyrrolidine-1-yl)benzonitrile derivative 2f as a clinical candidate. Issue 13 (1st July 2017) - Aikawa, Katsuji; Asano, Moriteru; Ono, Koji; Habuka, Noriyuki; Yano, Jason; Wilson, Keith; Fujita, Hisashi; Kandori, Hitoshi; Hara, Takahito; Morimoto, Megumi; Santou, Takashi; Yamaoka, Masuo; et al.
Graphical abstract: Abstract: We previously reported that 4-(pyrrolidin-1-yl)benzonitrile derivative1b was a selective androgen receptor modulator (SARM) that exhibited anabolic effects on organs such as muscles and the central nervous system (CNS), but neutral effects on the prostate. From further modification, we identified that 4-(5-oxopyrrolidine-1-yl)benzonitrile derivative2a showed strong AR binding affinity with improved metabolic stabilities. Based on these results, we tried to enhance the AR agonistic activities by modifying the substituents of the 5-oxopyrrolidine ring. As a consequence, we found that 4-[(2 S, 3 S )-2-ethyl-3-hydroxy-5-oxopyrrolidin-1-yl]-2-(trifluoromethyl)benzonitrile (2f ) had ideal SARM profiles in Hershberger assay and sexual behavior induction assay. Furthermore, 2f showed good pharmacokinetic profiles in rats, dogs, monkeys, excellent nuclear selectivity and acceptable toxicological profiles. We also determined its binding mode by obtaining the co-crystal structures with AR.